The methodological analysis of the measurement of vulnerability in Mexico / Análise metodológica da medição da vulnerabilidade no México - Luisi, Luis Alberto Olín Fabela; Ramírez, José Juan Méndez; Arteaga, Gustavo Álvarez (Revista de Direito da Cidade, 2020)
Abstract This paper performs an analysis based on the comparison between different methodologies that measure the vulnerability associated to hydrometeorological phenomena, in which the variables, indicators, and methods that use international methodologies offer as a result, an index that specifically measures vulnerability by integrating variables from social, economic and environmental dimensions through the Main Component Analysis Method, and if it is applied in Mexico according to methods used in the international environment would provide better results in the calculation of the vulnerability associated to hydrometeorological phenomena, with a methodology suitable to the Mexican case. Keywords: Vulnerability, Methodology, Hydrometeorological Phenomena, risk, disasters Resumo Este trabalho realiza uma análise a partir da comparação entre diferentes metodologias que medem a vulnerabilidade associada a fenômenos hidrometeorológicos, em que as variáveis, indicadores e métodos que utilizam metodologias internacionais oferecem como resultado, um índice que mede especificamente a vulnerabilidade por meio da integração de variáveis sociais, econômicas e ambientais através do Método de Análise de Componentes Principais. Se for aplicado no México segundo métodos utilizados no ambiente internacional, proporcionará melhores resultados no cálculo da vulnerabilidade associada aos fenômenos hidrometeorológicos, com uma metodologia adequada ao caso mexicano. Palavras-chave: Vulnerabilidade; Metodologia, Fenômeno hidrometeorológico, risco, desastres.